Early Intervention in the Recovery of Psychomotor Developmental Disorders in Preterm Infants – A Systematic Review Analysis - MOȚ, Raluca-Dana; ALMĂJAN-GUȚĂ, Bogdan (Studia Universitatis Babeș-Bolyai. Educatio artis gymnasticae, 2025)
Introduction: Preterm birth remains a major public health issue, being closely associated with a higher risk of psychomotor developmental disorders. Early physiotherapy interventions play a crucial role in supporting motor and cognitive development during the critical period of the first two years of life, with the potential to reduce long-term disability. Aim: The aim of this paper was to analyze and highlight the impact of early intervention in the recovery of psychomotor developmental disorders in preterm infants, through a systematic review of recent literature. Materials and Methods: This study is based on a systematic analysis of 20 scientific articles published between 2015 and 2025, identified using databases such as PubMed, Google Scholar, and Sci-Hub. Results: Individualized and multidisciplinary early interventions were found to be effective in improving motor, cognitive, and sensory development in preterm infants. Family-centered programs, therapies started during hospitalization or shortly after discharge, and combined interventions (such as sensory stimulation, infant massage, passive exercises, and hydrotherapy) led to significant developmental progress. Additionally, observational studies confirmed that preterm infants exhibit significant motor delays compared to full-term infants. Conclusion: The reviewed literature supports the effectiveness of early physiotherapy interventions in the recovery of preterm infants and emphasizes the need to implement such programs in Romanian clinical practice. Active family involvement, early initiation, and personalized approaches are essential to optimizing developmental outcomes in pre-term babies. Article history: Received 2025 July 27; Revised 2025 October 08; Accepted 2025 October 23;Available online 2025 November 20; Available print 2025 November 30